1983
DOI: 10.1111/j.1399-3054.1983.tb04201.x
|View full text |Cite
|
Sign up to set email alerts
|

Action of UV‐B radiation on photosynthetic primary reactions in spinach chloroplasts

Abstract: Spinach (Spinacia oleracea L. cv. Matador) chloroplasts were irradiated with several levels of UV‐B radiation. Measurements which reflect characteristic steps of photosynthetic electron transport were made to localize the site of impairment of photosynthesis by UV‐B radiation. Variable fluorescence, the μs‐kinetics of the 320 nm absorption changes and also oxygen evolution were substantially reduced in chloroplasts irradiated with UV‐B. It was not possible to restore the amplitude of the 320 nm absorption chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(64 citation statements)
references
References 25 publications
(21 reference statements)
0
64
0
Order By: Relevance
“…The common consequences on photosynthetic function are decreased CO 2 -fixation and oxygen evolution (Renger et al 1986;Allen et al 1997). This could be caused by several molecular events: While most studies have found that photosystem I (PS I) is only Rev Environ Sci Biotechnol minimally affected by UVB (by inhibiting PS I-mediated cyclic photophosphorylation; Iwanzik et al 1983;Renger et al 1986), photosystem II (PS II) seems to be a more important target (Bornman 1989). It is likely that UVB causes an inhibition of energy transfer within the PS II reaction centre by blocking electron flow.…”
Section: Biological Effects Of Uvbmentioning
confidence: 99%
“…The common consequences on photosynthetic function are decreased CO 2 -fixation and oxygen evolution (Renger et al 1986;Allen et al 1997). This could be caused by several molecular events: While most studies have found that photosystem I (PS I) is only Rev Environ Sci Biotechnol minimally affected by UVB (by inhibiting PS I-mediated cyclic photophosphorylation; Iwanzik et al 1983;Renger et al 1986), photosystem II (PS II) seems to be a more important target (Bornman 1989). It is likely that UVB causes an inhibition of energy transfer within the PS II reaction centre by blocking electron flow.…”
Section: Biological Effects Of Uvbmentioning
confidence: 99%
“…Numerous investigations have demonstrated that photosystem II (PSII) is the most sensitive component of the thylakoid membrane photosynthetic apparatus to increased exposure to UV-B (Noorudeen & Kulandaivelu 1982;Iwanzik et al 1983;Renger et al 1989;Kulandaivelu, Nedunchezhian & Annamalainathan 1991;Melis, Nemson & Harrison 1992). Consequently, PSII damage has often been implicated as the major potential limitation to photosynthesis in UV-B-treated leaves (Bomman 1989;Caldwell, Teramura & Tevini 1989;Stapleton 1992;Teramura & Sullivan 1994;Fiscus & Booker 1995), as is the case in the photoinhibition of photosynthesis by excess photosynthetically active radiation (380-700 nm) (Baker & Bowyer 1994), although it has been suggested that the mechanism of UV-B-induced damage may be different (Friso et al 1994;Jansen et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Although this predicted increase is small relative to the entire electromagnetic spectrum, UV-B has a disproportionately large photobiological effect due to its absorption by proteins and nucleic acids. In UV-B sensitive plants, photosynthetic capacity may be reduced directly by the effect of UV-B radiation on photosynthetic enzymes or disruption of PSII reaction centers, or indirectly by effects on photosynthetic pigments and stomatal function (9,13,19,20).…”
mentioning
confidence: 99%